URGENSI STRATEGI KOMUNIKASI DALAM MENUNJANG EFEKTIVITAS PENYELENGGARAAN PELAYANAN PUBLIK DI BPMPTSP KOTA PADANG - Helmi, Rahmadhona Fitri (TINGKAP, 2016)
Investment growth in Padang is inseparable from the role of BPMPTSP of Padang City which has the vision to create excellent invesment licensing service to increase the number of investment in Padang.This is certainly supported by the use of appropriate communication strategies.Various communication strategy that have been done by BPMPTSP to invite domestic investors (PMDN) and foreign investors (PMA) to invest in Padang is as follows;1) Issuance of Regional Regulation Incentive No.11 of 2009 which provides convenience to the public in making a license at BPMPTSP;2) licensing service mechanism is clear and in accordance with Standard Operational Procedure; 3) Upgrading the licensing service system by building an internet network that can be accessed by the public.The implementation of this communication strategy is quite successful which can be seen from the increasing number of local investors and foreign investors in Padang.Keywords: Comunication Strategy, BPMPTSP, Public Service, PMDN, PMA